PERENCANAAN SUMUR RESAPAN PADA GAMPONG LAMTEH BANDA ACEH - Hasanah Balqis, Salsabila; Rohendi, Aulia; Harahap, Juliansyah (Department of Environmental Engineering (Prodi Teknik Lingkungan), Fakultas Sains dan Teknologi, UIN Ar-Raniry Banda Aceh, 2023)
Changes in land use cause to reduced water absorption. Aceh Province is one of the areas that does not yet have technical regulations that have been implemented in terms of increasing water infiltration. This is one of the causes of not optimal flood handling. In urban areas, for example in the capital of Aceh Province, namely Banda Aceh, floods still occur frequently when there is high rainfall intensity and long duration of rain. One of the villages that experienced inundation was Gampong Lamteh, Ulee Kareng District, Banda Aceh. One solution to this problem is the construction of environmentally sound drainage in the form of infiltration wells. The existing drainage channels in Gampong Lamteh Banda Aceh are currently only located at a few points to drain excess water into water bodies while the rest are still ground canals. The cause of inundation is due to the unavailability of rainwater infiltration sites. After planning, the infiltration discharge value obtained by the infiltration wells is 0.000006594 m3/second and the total storage volume is 70,650 m3 and the design of the infiltration wells is planned in the form of a circle with a well height of 3 m, radius 0.5 m radius and the planned number of wells is 30 wells.